Advances in exogenous docosahexaenoic acid‐containing phospholipids: Sources, positional isomerism, biological activities, and advantages. Issue 4 (23rd May 2020) - Zhang, Yao; Wu, Gangcheng; Zhang, Yanjie; Wang, Xingguo; Jin, Qingzhe; Zhang, Hui
Abstract: In recent years, docosahexaenoic acid‐containing phospholipids (DHA‐PLs) have attracted much attention because of theirs unique health benefits. Compared with other forms of docosahexaenoic acid (DHA), DHA‐PLs possess superior biological effects (e.g., anticancer, lipid metabolism regulation, visual development, and brain and nervous system biochemical reactions), more intricate metabolism mechanisms, and a stronger attraction to consumer. The production of DHA‐PLs is hampered by several challenges associated with the limited content of DHA‐PLs in natural sources, incomplete utilization of by‐products, few microorganisms for DHA‐PLs production, high cost, and complex process of artificial preparation of DHA‐PLs. In this article, the sources, biological activities, and commercial applications of DHA‐PLs were summarized, with intensive discussions on advantages of DHA‐PLs over DHA, isomerism of DHA in phospholipids (PLs), and brain health. The excellent biological characteristics of DHA‐PLs are primarily concerned with DHA and PLs. The metabolic fate of different DHA‐PLs varies from the position of DHA in PLs to polar groups in DHA‐PLs. Overall, well understanding of DHA‐PLs about their sources and characteristics is critical to accelerate the production of DHA‐PLs, economically enhance the value of DHA‐PLs, and improve the applicability of DHA‐PLs and the acceptance of consumers.